The effect of inbreeding and hybridization on the seed ability of fababeans (Vicia Faba L.) - Lim, Eng Siong; Knight, R. (1980)
The flowers of fababeans may be self-pollinated or cross-pollinated and because of the mating system the crop cannot be exclusively treated as self or cross-pollinated in breeding programmes. Various levels of natural cross-fertilization have been reported but it is generally accepted that between 30 to 40% of the crop is produced from cross- pollination (Hua, 1943; Fyfe and Bailey, .1951; Rowlands, 1958; Holden and Bond, 1960). Cross-pollination is normally affected by bees. A bee entering a flower causes it to be tripped, that is the stigmatic column is released from the enveloping keel petals and the stigma is more fully exposed. If the bee carries foreign pollen the flower is cross- pollinated, but even if it does not, the tripping process may facilitate pod setting from self-pollination. A plant that is able to set pods following self-pollination is said to be self fertile. Some plants have the ability to set pods without tripping and are described as being autofertile.